Oeconomies in the Age of Newton. Economia civile and pubblica felicita in the Italian Enlighenment - PORTA, PIER LUIGI; BRUNI, LUIGINO ([Duke University Press], 2003)
This artiche contains the BASIC elements of the historiographic revision made by the authors, which has completely changed the approach to Politcal and Civil economy in the Italian Ennlightenment.